Poetry Kama Nasya’ Works of Samih Al-Qasim (Analysis of The Semiotic Riffaterre) - Irwan Mus (JOURNAL OF SOCIETY INNOVATION AND DEVELOPMENT, 2024)
The material object of this writing is the poetry of the Kama Nasya’ works of Samih al-Qasim, Palestinian poet and the object formal is a semiotic Riffaterre. In his theory, Michael Riffaterre introduce two levels of reading, namely the heuristic (the reading of mimetic, based on the dictionary meaning, characterized by (grammatical irregularities) and retroactive or hermeneutics (the reading process of decoding by finding the models, matrices, hipogram: potential and actual to get the unity of the meaning of the poem). The results of this study reveal that the poem Kama Nasya’ in the reading of heuristics is still scattered, fragmentary, and have not focused. In the reading of the retroactivity or hermeneutics, hipogram potential suggests the idea that the author have a supposition full of puzzles. Model (sentence monumental of poetry) is the sentence likun kama nasya’ in the ninth line rinse and the sentence is similar to the title selected by the author in his poem, namely Kama Nasya’. Matrices poetry that is ‘Nationalism’ a love of country. Hipogram the actual into the background of the formation of the matrix is the taste will be stirrings in his homeland attacked by Zionist Israel.